Lost In Translation? Challenges in Using Psychological Tests in the Philippines - Bernardo, Allan B. I. (Silliman Journal, 2022)
Filipino psychologists often use foreign-made psychological tests in English in their professional practice and in research. The paper raises questions on the validity of such tests for use with different Filipino respondents. Drawing from international standards for translating and adapting tests, the various levels of equivalence (qualitative and quantitative) between the original tests and their translations are discussed. The different types and sources of bias (construct, method, and item biases) that lead to non-equivalent translations of tests are also explained. The paper then reviews research on the equivalence of Filipino translations of tests with their original English versions and points to the strong possibility that the translations, as well as the English versions of the test used with Filipino participants, are not equivalent to the original tests used with the original target populations. The paper ends with a discussion of possible courses of action and the need for collective action from different sectors of the Filipino psychology community to address the concern.